Phylogeny and biodiversity of Trichoderma and Hypocrea and its implications on taxonomy - Christian P Kubicek (浙江大学学报. 农业与生命科学版)
Safe strain identification and species recognition is an important issue for Trichoderma and Hypocrea, because members of the genus are economically important producers of industrial enzymes and antibiotics, have application as biocontrol agents against plant pathogens, whereas some have become known as opportunistic pathogens of immunocompromised mammals and humans. However, classical approaches based on the use of morphological and phenetic characters have been difficult to apply, due to the plasticity of characters and the discordance of morphological and molecular evolution.The application of the genealogical concordance and phylogenetic species concept (GCPSC) has made is an attractive alternative to morphological species recognition, but has not been stringently applied to Hypocrea/Trichoderma. In this review, I shall explain the tools needed and strategy of this concept, and I will present examples where it has been recently used by us and others to confirm existing taxa and to detect new species in various clades and sections of Trichoderma. In addition, the present state of a global survey of biodiversity of Trichoderma and Hypocrea will be presented, and reviewed in relation to biogeography and the mode of speciation of this genus.